Analysis of the Role of Artificial Intelligence in Improving the Efficiency of Control Systems in Digital-Based MSMEs in Bandung City - Faizah Kamilah; Yoyo Arifardhani; Wiwik Budianti (Greenation International Journal of Economics and Accounting, 2025)
The development of artificial intelligence (AI) technology has opened new opportunities for digital-based Micro, Small, and Medium Enterprises (MSMEs) in improving the efficiency of management control systems. This study aims to analyze the role of AI in improving the efficiency of control systems in digital-based MSMEs in Bandung City. The method used is descriptive qualitative with a case study approach. Data were collected through in-depth interviews with 7 informants consisting of 5 digital MSME actors and 2 supporting informants from government and academic elements. Data analysis used the Miles & Huberman model through the stages of data reduction, data presentation, and conclusion drawing. The results show that AI contributes significantly to increasing the efficiency of management control in three main dimensions: predictive-based planning, automated operational implementation, and real-time data-based evaluation. Measurably, the adoption of AI can reduce raw material waste by up to 40%, cut administrative costs from IDR 6 million to IDR 2 million per month, and contribute to an average turnover growth of 28% higher than MSMEs that do not use AI. On the other hand, obstacles were found in the form of low digital literacy, dependence on internet infrastructure, and the risk of over-reliance. This study concludes that AI has shifted the paradigm of MSME management control from a manual and reactive approach to a proactive, accurate, and data-driven system.